Qira'at in Tafsir Al-Jalalayn: A Study of Qira'at Patterned Fi Qira'atin in Surah Al-Baqarah and Its Implications - Barkia, Zulfadhli Rizqi (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to explain the existence of qira'at with fi qira'atin pattern in Surah al-Baqarah in Tafsir Jalalayn with the theory of validity of qira'at and explain the implications of qira'at with fi qira'atin pattern on interpretation in Tafsir Jalalayn. This research uses descriptive analytical method, namely processing data with data collection techniques, then analyzing and describing it and then arranged systematically and in detail. The author collects verses in Tafsir Jalalayn which are interpreted with the Fi Qira'atin pattern in Surah Al-Baqarah. This study uses a qualitative approach that is library research. By using the theory of validity of qira'at, namely Sanad Mutawatir, in accordance with Rasm Uthmani and in accordance with the rules of Arabic. The results of this study have two findings: First, of the thirty-five readings with the pattern fi qira'atin in Surah al-Baqarah in Tafsir Jalalayn, in the aspect of sanad history, there are three qira'at that are not included in the Mutawatir qira'at (Qira'at Sab'ah and 'Asyrah), namely in Surah al-Baqarah verse 119 on the word ØªÙØ³Ù’Ø¦ÙŽÙ„Ù which is read ØªÙØ³Ù’Ø¦ÙŽÙ„Ù’, Surah al-Baqarah verse 165 on the word ØªÙŽØ·ÙŽÙˆÙŽÙ‘Ø¹ÙŽ which is read ØªÙŽØ·ÙŽÙ‘ÙˆÙŽÙ‘Ø¹ÙŽ, Surah al-Baqarah verse 254 on the word Ø¨ÙŽÙŠÙ’Ø¹ÙŒ , Ø®ÙÙ„ÙŽÙ‘Ø©ÙŒ ,Ø´ÙŽÙÙŽØ§Ø¹ÙŽØ©ÙŒ read Ø¨ÙŽÙŠÙ’Ø¹Ù , Ø®ÙÙ„ÙŽÙ‘Ø©Ù ,Ø´ÙŽÙÙŽØ§Ø¹ÙŽØ©Ù. While the other thirty-two examples are classified as qira'at Mutawatir. in the aspect of rasm utsmani there is only one letter al-Baqarah verse 259, namely the word ÙŠÙŽØªÙŽØ³ÙŽÙ†ÙŽÙ‘Ù‡Ù’ becomes ÙŠÙŽØªÙŽØ³ÙŽÙ†ÙŽÙ‘ . From the aspect of Arabic language rules, everything is in accordance even though there are three qira'at shahzah. Second, of the thirty-five readings with the pattern of fi qira'atin in Surah al-Baqarah in Tafsir Jalalayn, all of them in terms of interpretative implications are divided into two, namely first, the interpretative implications of the nature of hypocrites, The deception of Iblis, the Actors of Repentance and the expression of repentance, the help of ALLAH to the Children of Israel, the story of the Children of Israel, the Children of Israel's denial of the promise, the impact of fanaticism, the impact of fanaticism, Akidah (about revelation and nasikh mansukh revelation), Kaaba as the center of worship, Testament to descendants, Every nation has a Qibla, Recompense for the wrongdoer, Related to Fasting, Ethics of warfare, Hajj and Umrah regulations, The law of alcohol and gambling, The recommendation to spend in the way of Allah, Related to divorce, Divorce for unmarried wives, Provisions of wills, The recommendation to spend in the way of Allah, The day of resurrection, Recognizing the power of Allah, Ethics in transactions (proof), The process of transactions (payment). Second, the implications for Arabic grammar and Qira'ah, namely in QS Al-Baqarah verse 98, QS Al-Baqarah verse 117, QS Al-Baqarah verse 119, QS Al-Baqarah verse 124, QS Al-Baqarah verse 158, QS Al-Baqarah verse 254, QS Al-Baqarah verse 259.